A photonic crystal hydrogel suspension array for the capture of blood cells from whole blood. Issue 6 (27th January 2016) - Zhang, Bin; Cai, Yunlang; Shang, Luoran; Wang, Huan; Cheng, Yao; Rong, Fei; Gu, Zhongze; Zhao, Yuanjin
Abstract : A new type of PAAm inverse opal barcode particle that can capture and detect multiple types of blood cells is presented. Abstract : Diagnosing hematological disorders based on the separation and detection of cells in the patient's blood is a significant challenge. We have developed a novel barcode particle-based suspension array that can simultaneously capture and detect multiple types of blood cells. The barcode particles are polyacrylamide (PAAm) hydrogel inverse opal microcarriers with characteristic reflection peak codes that remain stable during cell capture on their surfaces. The hydrophilic PAAm hydrogel scaffolds of the barcode particles can entrap various plasma proteins to capture different cells in the blood, with little damage to captured cells.